2018
DOI: 10.1080/14767058.2018.1540582
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroid administration in late-preterm gestations: a cost-effectiveness analysis

Abstract: Objective-To evaluate whether administration of antenatal late-preterm betamethasone is costeffective in the immediate neonatal period. Study Design-Cost-effectiveness analysis of late-preterm betamethasone administration with a time horizon of 7.5 days was conducted using a health-system perspective. Data for neonatal outcomes, including respiratory distress syndrome (RDS), transient tachypnea of the newborn (TTN), and hypoglycemia, were from the Antenatal Betamethasone for Women at Risk for Late Preterm Deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, a recent cost-effectiveness analysis based on aggregate data from the ALPS trial used trial secondary outcomes of transient tachypnea of the newborn and respiratory distress syndrome as the measure of effectiveness. 36 The authors did not assess the primary outcome. Because the parent trial found no difference in respiratory distress syndrome, any model of costs and effectiveness of respiratory distress syndrome based on the parent trial would be unlikely to show economic desirability.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent cost-effectiveness analysis based on aggregate data from the ALPS trial used trial secondary outcomes of transient tachypnea of the newborn and respiratory distress syndrome as the measure of effectiveness. 36 The authors did not assess the primary outcome. Because the parent trial found no difference in respiratory distress syndrome, any model of costs and effectiveness of respiratory distress syndrome based on the parent trial would be unlikely to show economic desirability.…”
Section: Discussionmentioning
confidence: 99%
“… Decision tree model 2011 Cost per QALY Single payer Lifetime effects High (21/23) Gyamfi-Bannerman 2019 34 USA Multi-centre trial in tertiary hospital settings ACS (betamethasone) 34 weeks 0 days to 36 weeks 6 days To assess whether betamethasone compared with standard of care (without betamethasone) was cost-effective. Cost-effectiveness analysis based on a randomized trial 2015 Cost per respiratory morbidity a Third party funder First 72 hours of neonatal period High (20/22) Rosenbloom 2020 32 USA Multi-centre trial in tertiary hospital settings ACS (betamethasone) 34 weeks 0 days to 36 weeks 6 days Compare betamethasone administration versus no betamethasone administration in patients at risk of delivery in the late-preterm period. Cost-effectiveness analysis based on a randomized clinical trial 2017 Cost per QALY Health sector 7.5 days (median duration of neonatal admission in the trial) High (20.5/22) Antenatal corticosteroids in preterm birth (broad or unspecified gestation) Johnson 1981 35 USA Tertiary hospital ACS (betamethasone) 26-35 weeks Determine whether prenatal glucocorticoid administration decreased the cost of newborn intensive care as well as mortality in infants born prematurely.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published between 1981 and 2019, and were conducted in high-income (31 studies), upper-middle income (3 studies), and low-income (1 study) countries. Five of the studies on ACS related to administration prior to 34 weeks’ gestation, 26 , 27 , 28 , 29 , 30 , 31 three were on its use in the late preterm period (34 to <37 weeks’ gestation), 32 , 33 , 34 one studied both categories, 35 and two did not specify ( Table 1 ). 36 , 37 Eight of the studies on tocolytics for managing preterm labour examined the use of tocolytics for facilitating ACS administration, 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 and twelve studies related to tocolytic use for acute and maintenance tocolysis without explicit consideration of ACS ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 The cost-effectiveness of the administration of betamethasone based in individual trials is controversial, and it should be based in the best estimation of effectiveness. 95,96 Mainly LMICs still have significant challenges to provide safe and effective antenatal corticosteroid use, including ensuring accurate gestational age determination, establishing clear treatment guidelines, strengthening provider capacity, incorporating corticosteroid in national essential medicines lists, and monitoring use and outcomes. 97…”
Section: Discussionmentioning
confidence: 99%